2021
DOI: 10.3389/fneur.2021.757038
|View full text |Cite
|
Sign up to set email alerts
|

A National Representative, Cross-Sectional Study by the Hellenic Academy of NeuroImmunology (HEL.A.NI.) on COVID-19 and Multiple Sclerosis: Overall Impact and Willingness Toward Vaccination

Abstract: Background: In the context of the coronavirus disease 2019 (COVID-19) pandemic, the constant needs of people with multiple sclerosis (PwMS) and their caregivers were urgently highlighted.Aim: The present study aims to capture the effects of the COVID-19 pandemic in several aspects of the quality of life of PwMS, in perception and behavior to COVID-19 and multiple sclerosis (MS), as well as concerning healthcare, working conditions, and the willingness toward COVID-19 vaccination.Methods: This study is an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The survey showed that the participants had received vaccination-related information from HCWs, also in combination with a variety of other sources, as the most used source. This result corresponds to findings obtained in other similar surveys conducted in this and in other geographic areas [ 28 , 39 , 40 , 41 , 42 ]. Moreover, the results of the multinomial and multivariate logistic regression analysis demonstrated that HCWs were the most important communication source in disseminating accurate information about vaccinations aimed at mitigating the risk and other public health threats.…”
Section: Discussionsupporting
confidence: 92%
“…The survey showed that the participants had received vaccination-related information from HCWs, also in combination with a variety of other sources, as the most used source. This result corresponds to findings obtained in other similar surveys conducted in this and in other geographic areas [ 28 , 39 , 40 , 41 , 42 ]. Moreover, the results of the multinomial and multivariate logistic regression analysis demonstrated that HCWs were the most important communication source in disseminating accurate information about vaccinations aimed at mitigating the risk and other public health threats.…”
Section: Discussionsupporting
confidence: 92%
“…The underlying disparity could be attributed to uninsured individuals lacking primary care providers, who, therefore, enjoy fewer opportunities, are exposed to fewer reminders, and have limited convenient options for receiving the vaccine. Lo et al’s research indicated that counties with a higher number of primary care providers (PCP) per 100,000 population had higher COVID-19 vaccination rates [ 43 ], highlighting the crucial role of primary care providers as a trusted source of information in positively impacting vaccine acceptance [ 44 , 45 ]. Additionally, despite the COVID-19 vaccine being available at no cost, concerns about associated expenses may deter uninsured individuals from seeking vaccination [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey was concluded a month after the CDC and FDA approved the COVID-19 vaccine for infants, toddlers, and preschool children. During the data-collection period, reported infections increased from 2,367,077 (as of 2 April 2022) to 6,401,754 (as of 15 November 2022) [22], and the number of vaccinations that had been administered in Texas increased from 45,390,689 prior to the data-collection period to 50,672,487 (as of 16 November 2022) [23].…”
Section: Methodsmentioning
confidence: 99%
“…Presumably, the restrictions that the coronavirus disease dictated, especially social isolation and complete lockdown, might have had a negative impact on the behaviors of RND patients. Rare diseases are chronic conditions that could make patients more vulnerable to the stress-related harmful effects of the COVID-19 pandemic [ 35 ]. The feelings of anxiety and insecurity regarding the effective prevention of the SARS-CoV-2 infection could justify the restricted access to the public healthcare system, and hence our clinic.…”
Section: Discussionmentioning
confidence: 99%